KOMPETENSI KEPALA BAGIAN DI UNIVERSITAS TADULAKO - Abuna, Wagiman (Katalogis, 2018)
The research aimed at finding out and analyzing the competence of the section head in Tadulako University. The population of this research was 20 people as head of sections in Tadulako University. 4 of them were thenÂ selected as samples or informants and the head of personnel (BAUK) of Tadulako University was selected as the key informants. This was a qualitative research which data were collected through interview and documentation technique. The data were analyzed through (1) data editing, (2) data grouping, (3) meaning interpretation of the data, and (4) conclusions drawing and suggestions. The result showed the (1) The competence of the section head in motive factors, was not running properly, (2) The competence of the section head in traits factors had run properly, (3) The competence of the section head in factor of self-concept head run properly, (4) The competence of the section head in knowledge factor was not running properly. (5) The competence of the section head in skill factor had run properly.